Development of an Easy and Selective Approach for Determination of Titanium Dioxide in Commerical Cosmetics by UV-Vis Spectrophotometric Technique - Zarei, Ali Reza; Jokar, Faezeh; Mardi, Kobra (Jordan Journal of Pharmaceutical Sciences, 2021)
A simple and selective method was described for the determination of amount of titanium dioxide (TiO2) in cosmetics. The method is based on the complex formation of Ti(IV) with hydrogen peroxide in acidic media and monitoring the absorbance of the colored product by spectrophotometric technique at λmax= 407 nm. The effect of experimental parameters on the reaction was investigated and optimized. Under optimal conditions, the calibration graph was linear in the range of 5.0-100 µg mL-1 of Ti (IV) with the limit of detection of 3.0 µg mL-1. The validity of the method was evaluated by means of the data statistical analysis. For this purpose, the method was applied to the determination of titanium dioxide in cosmetics, and the results were statistically compared based on t- and F-tests with those obtained by the Inductively coupled plasma-atomic emission spectroscopy (ICP-AES). There was no significant difference between the mean values and the precisions of the two methods at the 95% confidence level. The results showed that the proposed method offers an accuracy and reliable approach for the determination of TiO2 in commercial cosmetics, and can be suggested as a routine method in quality control laboratories.